2016
DOI: 10.1021/acsami.6b04992
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically Arranging Gold Nanoparticles on DNA Origami for Molecular Logic Gates

Abstract: In molecular engineering, DNA molecules have been extensively studied owing to their capacity for accurate structural control and complex programmability. Recent studies have shown that the versatility and predictability of DNA origami make it an excellent platform for constructing nanodevices. In this study, we developed a strand-displacing strategy to selectively and dynamically release specific gold nanoparticles (AuNPs) on a rectangular DNA origami. A set of DNA logic gates ("OR", "AND", and "three-input m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…A major challenge associated with TEM is the need for an “electron-transparent” substrate, through which electrons can pass freely without absorption or scattering, something not essential for either SEM or AFM. As an example of the power of this method, Yang et al [ 117 ] used TEM to image the positions of DNA origami tiles with AuNPs to determine the state of AND and OR logic gates.…”
Section: Characterizationmentioning
confidence: 99%
“…A major challenge associated with TEM is the need for an “electron-transparent” substrate, through which electrons can pass freely without absorption or scattering, something not essential for either SEM or AFM. As an example of the power of this method, Yang et al [ 117 ] used TEM to image the positions of DNA origami tiles with AuNPs to determine the state of AND and OR logic gates.…”
Section: Characterizationmentioning
confidence: 99%
“…Nanoparticle assembly‐disassembly can be triggered by chemical signals processed through biomolecular logic gates representing a biocomputing nanoplatform for therapeutics and diagnostics . Biomolecular logic gates have been used to arrange dynamically gold nanoparticles on DNA origami . Assembling of gold nanoparticles has been demonstrated by using a pH‐responsive DNA nanomachine logically processing biomolecular input signals …”
Section: Macro/micro/nano‐mechanical Transduction Of Chemical Outputmentioning
confidence: 99%
“…[202] Biomolecular logic gates have been used to arrange dynamically gold nanoparticles on DNA origami. [203] Assembling of gold nanoparticles has been demonstrated by using ap H-responsive DNA nanomachine logically processingbiomolecular input signals. [204] Figure17A showst he biocatalytic cascade mimicking an OR logic gate.…”
Section: Atomicforce Microscopy (Afm) Transduction Of Chemical Outputmentioning
confidence: 99%
“…Although these works revealed that NPs can be well assembled with DNA origami statically, the dynamic operation of an NP/DNA origami device is still a concern for various researchers. Our previous study realized a NP/DNA origami system, in which AuNPs could be dynamically released from a DNA origami in response to specific DNA signals [41]. In this work, the yield of the output structure was not very high, because a monofunctionalized DNA/AuNP conjugate was hybridized with one extended strand from the origami template.…”
Section: Introductionmentioning
confidence: 96%